Bacillus anthracis co-opts nitric oxide and host serum albumin for pathogenicity in hypoxic conditions - St John, Stephen; Blower, Ryan; Popova, Taissia; Narayanan, Aarthi; Chung-Chul, Myung; Bailey, Charles L.; Popov, Serguei G. (Frontiers in Cellular and Infection Microbiology, 2013)
Bacillus anthracis is a dangerous pathogen of humans and many animal species. Its virulence has been mainly attributed to the production of Lethal and Edema toxins as well as the antiphagocytic capsule. Recent data indicate that the nitric oxide (NO) synthase (baNOS) plays an important pathogenic role at the early stage of disease by protecting bacteria from the host reactive species and S-nytrosylating the mitochondrial proteins in macrophages. In this study we for the first time present evidence that bacteria-derived NO participates in the generation of highly reactive oxidizing species which could be abolished by the NOS inhibitor L-NAME, free thiols, and superoxide dismutase but not catalase. The formation of toxicants is likely a result of the simultaneous formation of NO and superoxide leading to a labile peroxynitrite and its stable decomposition product, nitrogen dioxide. The toxicity of bacteria could be potentiated in the presence of bovine serum albumin. This effect is consistent with the property of serum albumin to serves as a trap of a volatile NO accelerating its reactions. Our data suggest that during infection in the hypoxic environment of pre-mortal host the accumulated NO is expected to have a broad toxic impact on host cell functions.